Networking Futures : The Movements against Corporate Globalization - Juris, Jeffrey S., 1971- (Book collections on Project MUSE., 2008)
This is an ethnographic account of how the anti-corporate globalization movement uses new technologies to organise itself, written by a participant im many of the biggest demonstrations of recent years. In addition to this, Juris provides a history of the movement and traces its roots.